KEPEMIMPINAN LURAH SUSAN JASMINE ZULKIFLI : PEMBUKTIAN KAPABILITAS LURAH HASIL SELEKSI TERBUKA PROVINSI DKI JAKARTA TAHUN 2013 - Al Kautsarah Hanifati; Priyatno Harsasto; Puji Astuti (Journal of Politic and Government Studies, 2016)
Leadership capability is an issue that is essential, therefore the governmentespecially Jakarta administration implemented through a policy regarding the recruitmentof public officials, especially at the office of headman is through Open Selectionheadman at Jakarta in 2013, it is expected that the system can be a solution to the problemof leadership in Indonesia. Leadership capability is so important because it willdemonstrate leadership skills in completing their obligations and rights, in addition to thevery complex problems of society today is a challenge of leadership capability moreoverheadman as street-level bureaucracy. The current leadership is needed not just matters ofa technical nature but also adaptive leadership that can solve the problems thatarise.Susan Zulkifli Jasmine headman who was appointed as the leader of an openselection process to be one example of leadership, capability headman Susan JasminZulkifli in living amid leadership responsibilities and rights as a leader is also a rejectionof his appointment as a headman in Lenteng Agung.This research was conducted with the aim to describe how the headmanLeadership Capability Susan Jasmine Zulkifli associated with leadership theories that arespecialized in the field of leadership capability. From the approach of this study is todescribe and analyze the existing problems in the field that is the rejection of the citizensLentengAgung, then how village chief Susan In Structural, Human resources, Politics andSymbolic accommodate it through its versatility and views of the versatility of the extentto which leadership headman Susan Methods Qualitative research is descriptive. Datatriangulation technique or triangulation of sources used in this study to obtain a morevalid data validity. Sources of primary data obtained through interviews with relevantinformants and secondary data obtained from documents, records, internet, and othersources that are related to this research.Results of this study illustrate that leadership headman Susan Jasmine Zulkifli inthe Village Lenteng Agung General has shown versatility viewed from variousperspectives relating namely structural, human resource, political and symbolic later inview of its capabilities turned out leadership headman Susan has entered a level ofleadership adaptive it is evident from the Village Head Susan capability inaccommodating the conflict. From this research, it is known that the village chief SusanJasmine Zulkifli has adaptive capability as headman.Recommendations can be given them so that the government can assess howmuch risk arising from a policy and be able to anticipate these risks, then for Leadersmust have not only the expertise technically but also leadership skills adaptively whichmay face risks that arise in order to remain carry out its obligations in accordance withapplicable law and to the community ynag not expected to see a leader of a religiousbackground, ethnicity and culture because of the Pancasila state and has a legal basis butto see the leader of the capability to solve problems and carry out their duties in theirworking area.Keywords: Leadership capability, Adaptive Leadership, Head SusanJasmine Zulkifli, Lenteng agung